Places of well-being in a French region. Lyon residents and their preferences - Bourdeau-Lepage, Lise; Fujiki, Kenji (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
This paper seeks to reveal the key territorial components of people’s well-being. To this end, a method that makes it possible to (1) identify the components that potentially constitute well-being within a given territory and (2) determine, on the basis of individuals’ reported preferences, those areas that are most or least likely to meet these individuals’ needs has been developed and used. It reveals that natural amenities, access to health services, and safety are the most important factors for Lyon residents’ well-being. Taking as our starting point the preferred territorial components of Lyon residents, we identify the areas where their well-being would be greatest.